Cognitive Load Theory: Mathematical Resilience in a Variable Examples-Based Learning - Yohanes, Barep; Mutimmah, Dzurotul (Jurnal Pendidikan MIPA, 2023)
Cognitive load theory is an instructional design theory which emphasizes the limited nature of working memory's capacity to process information. Germane cognitive load supports learning in which students do continuous efforts in understanding learning materials. Continuous efforts to get the desired results are called resilience. The fact is that prospective Mathematics teachers have limited interest in understanding difficult material while interest is very closely related to resilience. This limited interest results in less optimal efforts. This research is a qualitative descriptive study which aims at describing aspects of resilience in Germane cognitive load-based learning by using variable examples. The findings showed that the stages of learning based on cognitive load with variable examples were giving orientation to the learning material, organizing the variable examples, giving assistance to the work completion, presenting the results, and evaluating. As conclusion, aspects of resilience that appear in cognitive load-based learning are perseverance, adaptiveness, creativity, self-motivation, curiosity, and self-control. Keywords: cognitive load, resilience, variable examples-based learning. DOI: http://dx.doi.org/10.23960/jpmipa/v24i2.pp493-504